2011
DOI: 10.1144/m35.35
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 35 Regional seismic interpretation of crustal framework, Canadian Arctic passive margin, Beaufort Sea, with comments on petroleum potential

Abstract: Three new regional 2D seismic surveys in the Beaufort Sea provide a broad, deeper view of basins and crustal structure of the Meso-Cenozoic Canadian Arctic passive margin. The seismic profiles cover 16 270 km from inner shelf to over 2000 m water depth and include areas previously unsurveyed due to sea-ice limits. The surveys cover offshore Mackenzie Delta and extend north to Latitude 748N off Banks Island. Geological interpretation is tied to exploratory wells in the Beaufort-Mackenzie Basin that has yielded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 20 publications
3
14
0
1
Order By: Relevance
“…Basin (Helwig et al, 2011), as also reported at many other passive margins. As already pointed out by previous authors (e.g., Scrutton 1982), the Free-Air gravity highs are produced by the combination of two factors: 1) the edge effect associated with crustal thinning from the continental to the oceanic domain, and 2) the presence of either a basement high or a high density zone along the outer shelf break.…”
Section: Discussion Of Residual Gravity Field and Densitysupporting
confidence: 81%
“…Basin (Helwig et al, 2011), as also reported at many other passive margins. As already pointed out by previous authors (e.g., Scrutton 1982), the Free-Air gravity highs are produced by the combination of two factors: 1) the edge effect associated with crustal thinning from the continental to the oceanic domain, and 2) the presence of either a basement high or a high density zone along the outer shelf break.…”
Section: Discussion Of Residual Gravity Field and Densitysupporting
confidence: 81%
“…The 80-Ma terminal collision aligns quite well with the main bulk of the mantle slab anomaly (Fig. 3), except for deviations within the Canadian sector, which were possibly caused by anticlockwise rotation of northern Alaska during the opening of the Canada Basin between 134 Ma and 84 Ma (Helwig et al 2011).…”
Section: Plate Trajectories and Paleomagnetismsupporting
confidence: 57%
“…(1) The Canada Basin probably had been formed before the Mid Aptian in the Early Cretaceous [Miller, Hudson, 1991;Helwig et al, 2011;Nikishin et al, 2014;Chain et al, 2016], though this issue remains debatable.…”
Section: Discussionmentioning
confidence: 99%